2016
DOI: 10.1016/j.lithos.2016.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Trace element composition of silicate inclusions in sub-lithospheric diamonds from the Juina-5 kimberlite: Evidence for diamond growth from slab melts

Abstract: Trace element composition of silicate inclusions in sublithospheric diamonds from the juina-5 kimberlite: Evidence for diamond growth from slab melts, LITHOS (2016), doi: 10.1016/j.lithos.2016.08.035 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 93 publications
4
25
0
Order By: Relevance
“…Such a model predicts that inclusion assemblages are chemically linked although they appear to reflect different host rocks, and that there should be straightforward elemental and isotopic patterns consistent with the evolution of conditions from the eclogite source to the ambient mantle. This model better explains the highly enriched character of inclusion minerals, which are otherwise anomalous if they are direct samples of the slab 76 . It also explains C-O stable isotopic systematics 77 .…”
Section: Box 3 Fig 1 | Schematic Representation Of Carbon Inputs Oumentioning
confidence: 94%
“…Such a model predicts that inclusion assemblages are chemically linked although they appear to reflect different host rocks, and that there should be straightforward elemental and isotopic patterns consistent with the evolution of conditions from the eclogite source to the ambient mantle. This model better explains the highly enriched character of inclusion minerals, which are otherwise anomalous if they are direct samples of the slab 76 . It also explains C-O stable isotopic systematics 77 .…”
Section: Box 3 Fig 1 | Schematic Representation Of Carbon Inputs Oumentioning
confidence: 94%
“…In most experimental studies, the distribution of REE between mantle perovskites and melt is considered. In particular, very low bridgmanite/melt REE partitioning coefficients calculated for the high-pressure conditions (~10 −3 for La to~1 for Lu) [23] suggest the primary origin of Brd grains with their further trapping by host superdeep diamonds, but not crystallization of bridgmanite from melt, as is suggested in some studies [24]. In contrast, CaSiO 3 -perovskite/melt partition coefficients for REE are much higher [25], which causes the higher concentrations of REE (by up to two to three orders of magnitude) with significant enrichment in LREE in natural CaPrv in relation to Brd.…”
Section: Discussionmentioning
confidence: 96%
“…Wang et al 174 suggested a role for carbonated melt in the origin of Ca-perovskite inclusions, and the distinct trace element patterns in Ca-perovskite and majorite inclusions from Juína, Brazil, indicate that the inclusions crystallized from carbonated melt derived from subducted oceanic crust. 20,21,56,176,189 The involvement of recycled crustal components in the origin of super-deep diamonds is supported by observations that the diamond hosts show a wide range of carbon isotope compositions extending to very light values (e.g.~0% to -25%) 20,21 and that majorite garnet and other silicate inclusions have isotopically heavy oxygen isotope compositions. 104,109 The high and variable ferric iron content of majorite inclusions is also consistent with an oxidized carbonate component in their origin.…”
Section: Diamond Growth By Redox Freezing From Carbonated Melts In Thmentioning
confidence: 95%
“…Refs. 18,20,21,49,56,98,100,102,105,118,[174][175][176]. Inclusions interpreted as former majorite garnet or Ca-perovskite often exhibit composite mineralogy that is interpreted to have formed by unmixing from primary precursor minerals exhibiting solid solution (e.g.…”
Section: Diamond Growth By Redox Freezing From Carbonated Melts In Thmentioning
confidence: 99%